Phormidium subfuscum Kütz. ex Gomont ... - Gupta, Pratibha (Zenodo, 2021)
Phormidium subfuscum Kütz. ex Gomont Phycologia generalis : 195 (Kützing 1843). Tiffany & Britton, The Algae of Illinois 332, t. 90, f. 1044 (Tiffany & Britton 1952). Desikachary, Cyanophyta 273, t. 44, f. 22-23 (Desikachary 1959). DESCRIPTION. — Trichome straight, blue-green or sometimes olive-green, not constricted at the cross-walls, generally cross-walls granulated, slightly narrow apically, sometimes sub-quadrate; end more or less briefly attenuated, capitate; end cells straight, acuteconical (Fig. 8L). DIMENSION. — Trichome 5.4-11.0 µm broad and cells 2.1-3.9 µm long. ENVIRONMENT & HABITAT. — Freshwater species; stagnant water; temperature 1°C. ... : Published as part of Gupta, Pratibha, 2021, First report of diversity of Cyanobacteria of Broknes Peninsula of Larsemann Hills, East Antarctica, pp. 241-251 in Cryptogamie, Algologie 20 (15) on page 247, DOI: 10.5252/cryptogamie-algologie2021v42a15, http://zenodo.org/record/7819309 ...